Desecularizing the Christian past : beyond R.A. Markus and the religious-secular divide - Beltramini, Enrico (Amsterdam University Press, 2023)
The essential objective of this study is to unpack the complicity between historians and secularization theory in the study of late ancient and early medieval Christianity-and then suggest a way out. In this work of historiography of religion, Enrico Beltramini argues that religious history is inherently secular and produces distorted representations of the Christian past. He suggests moving from an epistemological to a hermeneutical approach so that the supernatural worldview of the Christian past can be addressed on its own terms. This work also engages Markus's saeculum and replaces Markus's secularized relationship between the Kingdom and the government of the civitas with the Augustinian association of the Kingdom and divine government.
FOREWORD ACKNOWLEDGEMENTS ABBREVIATIONS INTRODUCTION SACRAMENTAL ONTOLOGY ONTOLOGICAL TURN HISTORY AND THEOLOGY SAECULUM ANCIENT AND MODERN CHRISTIANITY AUGUSTINIANISMS SAECULUM RETOLD CONCLUSION BIBLIOGRAPHY
Keywords: Markus, R. A. -- (Robert Austin), -- 1924-2010.; Church history -- Historiography.; Église -- Histoire -- Historiographie.; History: theory and methods.; Early history: c. 500 to c. 1450/1500.; Christianity.; HISTORY / Medieval.; RELIGION / Christianity / History.; RELIGION / Christian Church / History.; HISTORY / Europe / Medieval; Church history -- Historiography; Historical research: source documents.; European history: medieval period, middle ages.; Roman Catholicism, Roman Catholic Church.; History, Art History, and Archaeology; HIS; Antiquity; ANTIQ; History; Medieval Studies; MEDIEVAL; Religion and Theology; REL & THEOL; Religious History, Historical Methodology, Middle Ages, Gregory the Great, Augustine of Hippo